Computer-Aided Stereolithography for Presurgical Planning in Fibula Free Tissue Reconstruction of the Mandible - Sink, Jill; Hamlar, David; Kademani, Deepak; Khariwala, Samir S. (Journal of Reconstructive Microsurgery, 2012)
Introduction Computer-aided imaging has facilitated presurgical modeling for free tissue mandibular reconstruction. The purpose of this study is to illustrate the utility of preoperative virtual surgical planning in fibula reconstruction of the mandible.Methods Eight patients, age 17 to 72 years, treated between November 2009 and January 2011 were reviewed. Each required segmental resection and reconstruction of the mandible and were managed with presurgical virtual planning.Results Our series includes five cases of squamous cell carcinoma (SCCA), one case of osteoradionecrosis (ORN), one leiomyosarcoma, and one odontogenic myxoma. All patients underwent a segmental resection of the mandible 5 to 14 cm in size (average 8 cm). In each case, prefabricated guides for segmental mandibulectomy and fibula osteotomy were employed and resulted in simplification of bony inset and reduced need for “fine tuning” of fibula segments.Conclusions Virtual surgical planning fosters multidisciplinary communication and provides accurate presurgical planning. This allows seamless reconstruction in patients requiring mandibular reconstruction via fibula free tissue transfer. The combination of mandibular and fibular cutting guides and templates allows for a precise and efficient surgical reconstruction. In our experience, this technology is most useful in the reconstruction of large mandibular defects requiring large reconstruction plates and multiple fibular osteotomies.
Keywords: fibula; free flap; mandibular reconstruction; modeling